Tilting plane tests for the ultimate shear capacity evaluation of perforated dry joint masonry panels. Part II: Numerical analyses. (1st February 2021) - Grillanda, Nicola; Chiozzi, Andrea; Milani, Gabriele; Tralli, Antonio
Highlights: Numerical reproduction of tilting plane tests on in-scale perforated masonry walls. Utilization of associated and non-associated heterogeneous limit analysis approach. Analogy with Linear Programming problem in presence of settlements. Sensitivity analyses with imperfection of the brick geometry and installation defects. Very good agreement between numerical and experimerimental failure mechanisms observed. Abstract: Within the student competition that took place during the 10th International Masonry Conference (10th IMC, 9–11 July 2018, Technical University of Milan, Milan, Italy), a set of tilting plane tests on dry joint masonry shear panels were carried out. Several tests were conducted by means of a tilting table: in-scale models of different perforated masonry shear walls were inclined until the activation of a global collapse mechanism. The ultimate inclination angle is always representative of the maximum shear force that the structure can bear. A total of 7 wall designs WDs, each one proposed by a student team according to some imposed geometrical criteria (8 bricks length, 27 bricks height, 30% minimum percentage of openings), was tested. In this work, numerical simulations aimed at reproducing experimental results obtained during the competition are presented. The problem is studied both in terms of rigid body structures subjected to a finite base rotational settlement and by means of traditional limit analysis. The finite settlement problem is treated incrementally, i.e. by increasing through a small amount the base rotational settlement at each step. On the other hand, limit analysis is performed assuming both associative and non-associative behavior for the masonry material. Finally, in order to better represent the actual behavior of walls during experiments, some simple strategies aimed at including within the numerical models some geometrical imperfections of the bricks and installation defects are devised and their effects are evaluated by means of sensitivity analyses.